An exploration of the folding and assembly requirements of diverse bacterial rubiscos - Ramya, Ramaswamy Chettiyan Seetharaman (2019)
Ribulose 1, 5-bisphosphate carboxylase/oxygenase (Rubisco) is the most abundant enzyme representing the main gateway of inorganic carbon into the biosphere by catalysing CO2-fixation during photosynthesis. In spite of its pivotal role, the enzyme has poor kinetics and substrate specificity. Structurally, Rubisco exists in different forms ranging from dimers of large subunits to hexa-decamers of large and small subunits. These structurally distinct Rubiscos utilize complex machinery for biogenesis including a multiverse of chaperones. It is our aim to devise a simple in vitro method to investigate the folding and assembly requirements for different forms of Rubisco. An understanding of in vitro Rubisco reconstitution will provide critical information on additional components required for successful Rubisco re-engineering in in vivo systems, knowledge of which will help in producing platforms for recombinant expression of heterologous Rubisco systems. To this end we have adopted the continuous spectrophotometric Rubisco activity assay to quantitatively evaluate folding and assembly kinetics in addition to specific chaperone requirements of different Rubisco systems. Chaperonin GroEL/GroES and Mg-ATP are necessary and sufficient for both dimeric and hexameric form II Rubisco, consisting only of large subunits, to fold and assemble from denatured subunits. It was observed that the dimeric Rhodospirillum rubrum form II Rubisco had a more rapid maturation rate compared to the hexameric Acidithiobacillus ferrooxidans form II Rubisco likely due to the requirement for higher order oligomerization of the hexamer. Interestingly, in contrast to the well-studied chaperone dependent form I cyanobacterial Rubisco, the assembly of the hexadecameric proteobacterial form I Acidithiobacillus ferrooxidans Rubisco occurs independently of ancillary proteins. Instead, it requires only the small subunits to assemble into the functional hexa-decamers following successful folding by GroEL/GroES. In conclusion, our method will permit systematic in vitro screening and determination of conditions that allow comparative assessment of folding and assembly of all forms of Rubiscos. Simultaneously, we are aiming at constructing Rubisco engineering platforms using a cyanobacterial system, a well-established model organism for photosynthetic research. We have generated cyanobacterial strains (termed cyano-red) using Synechocystis sp. PCC 6803 in which the form IC red-type Rubisco from Rhodobacter sphaeroides along with its activase is expressed, folded and assembled properly. Further biochemical and physiological characterization of this cyano-red strain will provide us with novel insights on the biogenesis of different Rubiscos using this cyanobacterial platform.